2016
DOI: 10.1177/0022429416639232
|View full text |Cite
|
Sign up to set email alerts
|

Singer Perceptions of Collegiate Mid-Level Choral Experiences

Abstract: In this descriptive study, researchers surveyed choristers ( N = 630) from 16 mid-level collegiate choirs nationwide to investigate their perceptions and behaviors as they related to the strategies used by directors to facilitate ensemble identity. Also investigated were the factors affecting choristers’ dedication to choir and their intentions regarding future enrollment in the choral program. Results indicated that mid-level collegiate choristers hold very diverse opinions regarding the effectiveness of dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Finally, recent studies, such as that of Major and Dacon (2016), which surveyed 630 choristers out of 16 middle school choirs, also indicated that singers who wanted to remain in their choir were backed by the influence of personal and external factors followed by musical factors (such as the repertoire, the choir’s talent, among others).…”
Section: Singers’ Motivation In Relation To Musical Activitiesmentioning
confidence: 99%
“…Finally, recent studies, such as that of Major and Dacon (2016), which surveyed 630 choristers out of 16 middle school choirs, also indicated that singers who wanted to remain in their choir were backed by the influence of personal and external factors followed by musical factors (such as the repertoire, the choir’s talent, among others).…”
Section: Singers’ Motivation In Relation To Musical Activitiesmentioning
confidence: 99%
“…This was especially salient in the Advanced Women’s Choir context. In this setting, there were fewer “stayers” and more “stayer-movers” and “movers” (Major & Dakon, 2016). Though almost all participants expressed that high school women’s choirs could perform as well or better than mixed choirs, similar to Gauthier (2005), they also stated their next goal was to sing in the mixed choir because it was the perceived highest point of the choral hierarchy, and they thought they would enjoy a mixed choir atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson (2012) found high school participants enjoyed the challenges of women's choir contexts, and confirmation from concert audiences bolstered participants' self-worth in the ensemble. Even with audience recognition, however, Wilson reported that women's choirs were perceived as preparation for the select mixed choir ensemble, a finding articulated by other researchers, including Gauthier (2005), O'Toole (1998, and Major and Dakon (2016).…”
mentioning
confidence: 96%
See 2 more Smart Citations